Effect of a brain‐penetrant selective estrogen receptor degrader (SERD) on binge drinking in female mice. (29th May 2022) - Chen, Hu; Lu, Yunlong; Xiong, Rui; Rosales, Carlo I.; Coles, Cassandre; Hamada, Kana; Asad, Nuria; Thatcher, Gregory R. J.; Lasek, Amy W.
Abstract: Background: Greater circulating levels of the steroid hormone 17β‐estradiol (E2) are associated with higher levels of binge drinking in women. In female mice, estrogen receptors in the ventral tegmental area, a dopaminergic region of the brain involved in the motivation to consume ethanol, regulate binge‐like ethanol intake. We recently developed a brain‐penetrant selective estrogen receptor degrader (SERD), YL3‐122, that could be used to test the behavioral role of brain estrogen receptors. We hypothesized that treating female mice with this compound would reduce binge‐like ethanol drinking. Methods: Female C57BL/6J mice were treated systemically with YL3‐122 and a related SERD with low brain penetrance, XR5‐27, and tested for binge‐like ethanol consumption in the drinking in the dark (DID) test. Mice were also tested for sucrose and water consumption and blood ethanol clearance after treatment with the SERDs. Finally, the effect of ethanol exposure on Esr1 gene expression was measured in the ventral tegmental area (VTA), prefrontal cortex (PFC), and ventral hippocampus (vHPC) of male and female mice by quantitative real‐time PCR after 4 DID sessions. Results: YL3‐122 reduced ethanol consumption when mice were in diestrus but not estrus. YL3‐122 also decreased sucrose consumption but did not alter water intake or blood ethanol clearance. XR5‐27 did not affect any of these measures. Binge‐like ethanol drinking resulted in increased Esr1 transcript in the VTA of both sexes, male vHPC, and female PFC. Conclusions: These results indicate that SERD treatment can decrease binge‐like ethanol drinking in female mice. Thus, it could be a novel strategy to reduce binge drinking in women, with the caveat that effectiveness may depend on menstrual cycle phase. In addition, Esr1 transcript is increased by binge ethanol exposure in both sexes but in a brain region‐specific manner. Abstract : Estradiol has been shown to promote binge‐like drinking in female mice. Compounds known as selective estrogen receptor degraders (SERDs) inhibit the activity and promote degradation of estrogen receptors. Here, we demonstrated that treatment with a novel oral, brain‐bioavailable SERD, YL3‐122, reduced binge‐like ethanol intake in female mice in diestrus but not estrus, whereas treatment with a related SERD with low brain penetrance, XR5‐27, had no effect. We also found that Esr1 expression increased in mouse brain after binge ethanol intake.